Anesthetic and Analgesic Management for Mastectomy of a Giant Phyllodes Tumor: A Case Report on the Central Role of the Serratus Anterior Plane Block - Heri Dwi Purnomo; Bara Aditya; Yasyfie Asykari; Rafael Bagus Yudhistira (HM Publisher, 2025)
Mastectomy for giant breast tumors presents a formidable clinical challenge due to the anticipated extensive surgical trauma, significant inflammatory response, and high risk of severe postoperative pain. This intense nociceptive barrage can lead to central sensitization and the development of debilitating Post-Mastectomy Pain Syndrome (PMPS). A robust, opioid-sparing multimodal analgesic strategy is therefore not just beneficial, but essential. The Serratus Anterior Plane Block (SAPB) is a regional anesthetic technique integral to such a strategy. We present the case of a 39-year-old, 60 kg female with a giant (24 x 22 x 18 cm) right-sided phyllodes tumor scheduled for mastectomy. The anesthetic plan consisted of general anesthesia and a preemptive, ultrasound-guided deep SAPB using 20 mL of 0.25% levobupivacaine. The procedure was performed with meticulous attention to sonoanatomy and technique. Intraoperatively, the patient maintained profound hemodynamic stability with minimal requirement for volatile anesthetic. Postoperatively, the patient reported complete analgesia, with Visual Analog Scale (VAS) scores of 0 at rest and 0-1 with movement (dynamic pain) for the first 24 hours. Sensory testing confirmed a dense block from T2 to T7. The patient required no rescue analgesia, mobilized early, and reported high satisfaction with her recovery. The final pathology confirmed a borderline phyllodes tumor. In conclusion, this case report demonstrates that a meticulously performed, ultrasound-guided deep SAPB can serve as the cornerstone of an effective, opioid-sparing analgesic regimen for high-pain-risk breast surgery. It can provide complete and functional postoperative analgesia, enhance hemodynamic stability, and facilitate recovery, embodying the core principles of Enhanced Recovery After Surgery (ERAS) pathways.